Is Focal Cortical Dysplasia/Epilepsy Caused by Somatic MTOR Mutations Always a Unilateral Disorder?. (February 2021) - Guerrini, Renzo; Cavallin, Mara; Pippucci, Tommaso; Rosati, Anna; Bisulli, Francesca; Dimartino, Paola; Barba, Carmen; Garbelli, Rita; Buccoliero, Anna Maria; Tassi, Laura; Conti, Valerio
Abstract : Objective: To alert about the wide margin of unpredictability that distribution of somatic MTOR mosaicism may have in the brain and the risk for independent epileptogenesis arising from the seemingly healthy contralateral hemisphere after complete removal of epileptogenic focal cortical dysplasia (FCD). Methods: Clinical, EEG, MRI, histopathology, and molecular genetics in 2 patients (1 and 2) treated with focal resections and subsequent complete hemispherectomy for epileptogenic FCD due to somatic MTOR mutations. Autoptic brain study of bilateral asymmetric hemispheric dysplasia and identification of alternative allele fraction (AAF) rates for AKT1 (patient 3). Results: The strongly hyperactivating p.Ser2215Phe (patient 1) and p.Leu1460Pro (patient 2) MTOR mutations were at low-level AAF in the dysplastic tissue. After repeated resections and eventual complete hemispherectomy, both patients manifested intractable seizures arising from the contralateral, seemingly healthy hemisphere. In patient 3, the p.Glu17Lys AKT1 mutation exhibited random distribution and AAF rates in different tissues with double levels in the more severely dysplastic cerebral hemisphere. Conclusions: Our understanding of the distribution of somatic mutations in the brain in relation to the type of malformation and its hypothesized time of origin may be faulty. Large studies may reveal that the risk of a first surgery being disappointing might be related more to the specific somatic mammalian target of rapamycin mutation identified than to completeness of resection and that the advantages of repeated resections after a first unsuccessful operation should be weighed against the risk of the contralateral hemisphere becoming in turn epileptogenic.